2016
DOI: 10.1021/acs.jmedchem.6b00126
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin 2.0: Adjusting Key Levers for Metabolic Stability

Abstract: The 52 amino acid peptide hormone adrenomedullin (ADM) plays a major role in the development and regulation of the cardiovascular and lymphatic system and has therefore gained significant interest for clinical applications. Because adrenomedullin exhibits low metabolic stability, enhancement of the plasma half-life is essential for peptide-based drug design. Fluorescently labeled ADM analogues synthesized by Fmoc/t-Bu solid phase peptide synthesis were used to analyze their enzymatic degradation and specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(75 citation statements)
references
References 48 publications
(139 reference statements)
5
70
0
Order By: Relevance
“…Adrenomedullin represents ap romising starting point for selectivity research, as it already possesses ad istinct intrinsic preference for the AM 1 Ra nd the AM 2 Ro ver the CGRPR. [26] Amino acids of the activation motif of a-CGRP were introduced into ADM as af irst step. [17,18,25] Because earlier studies also demonstrated that this analogue exhibits the same selectivity profile as the full-length wild-type, it was used as al ead peptide foro ur investigations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adrenomedullin represents ap romising starting point for selectivity research, as it already possesses ad istinct intrinsic preference for the AM 1 Ra nd the AM 2 Ro ver the CGRPR. [26] Amino acids of the activation motif of a-CGRP were introduced into ADM as af irst step. [17,18,25] Because earlier studies also demonstrated that this analogue exhibits the same selectivity profile as the full-length wild-type, it was used as al ead peptide foro ur investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Olefins tapled analogues of 1 were synthesized using (S)-2-(4-pentenyl)alanine staplinga tt he N-terminal (23)(24)(25)(26)(27)10)o r the C-terminal end of the helix (26)(27)(28)(29)(30)11)i no rder to study whether the position of the stabilizing modification makes a difference. Olefins tapled analogues of 1 were synthesized using (S)-2-(4-pentenyl)alanine staplinga tt he N-terminal (23)(24)(25)(26)(27)10)o r the C-terminal end of the helix (26)(27)(28)(29)(30)11)i no rder to study whether the position of the stabilizing modification makes a difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations